Strategic Management for Long-term Sustainability in Higher Education Institutions - Dodhy Hyronimus; Adiatma, Tini (Nusantara Journal of Multidisciplinary Science, 2024)
The purpose of writing this article is to find out references regarding strategic management in higher education. This research was conducted using the Systematic Literature Review method. The articles used were obtained from the Scopus database with a specific search, namely "strategic management in higher education". The results of the search revealed that there were 18 articles from 1999 to 2023. These results indicate that this keyword is still little used as a title in existing research. This research was conducted from various countries, namely England, USA, India, Sweden, Russia and Indonesia, Chile, Portugal, Jamaica, Poland, Vietnam, Ecuador and the United Arab Emirates. Articles are written using various research methods, but are generally presented as case studies. The research results show the diversity of discussions in strategic management carried out in higher education institutions. The article also covers concepts and implementation in strategic management in higher education. It is hoped that this article will provide an overview of research areas that can still be developed regarding management strategies in higher education.